2019
DOI: 10.1021/acsami.9b12018
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Indoor Organic Solar Cells by Voltage Loss Minimization through Fine-Tuning of Polymer Structures

Abstract: Herein, we report a detailed study on the optoelectronic properties, photovoltaic performance, structural conformation, morphology variation, charge carrier mobility, and recombination dynamics in bulk heterojunction solar cells comprising a series of donor–acceptor conjugated polymers as electron donors based on benzodithiophene (BDT) and 5,8-bis­(5-bromothiophen-2-yl)-6,7-difluoro-2,3-bis­(3-(octyloxy)­phenyl)­quinoxaline as a function of the BDT’s thienyl substitution (alkyl (WF3), alkylthio (WF3S), and flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…[18] Singh et al investigated the substituent effects on the performance of donor based on benzodithiophene (BDT) and 5,8-bis(5-bromothiophen-2-yl)-6,7difluoro-2,3-bis(3-(octyloxy)phenyl)quinoxaline. [30] As a result, the fluorine substituent (WF3F) on the BDT thienyl showed great improvement in properties when compared with alkyl-(WF3) and alkylthio-(WF3S) substituents, showing a larger optical bandgap. Under 1 sun illumination, WF3:PC 71 BM, WF3S: PC 71 BM, and WF3F:PC 71 BM OSCs with diphenyl ether (DPE) additive exhibited PCEs of 7.71, 7.91, and 9.11 %, respectively.…”
Section: Binary Fullerene-based Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Singh et al investigated the substituent effects on the performance of donor based on benzodithiophene (BDT) and 5,8-bis(5-bromothiophen-2-yl)-6,7difluoro-2,3-bis(3-(octyloxy)phenyl)quinoxaline. [30] As a result, the fluorine substituent (WF3F) on the BDT thienyl showed great improvement in properties when compared with alkyl-(WF3) and alkylthio-(WF3S) substituents, showing a larger optical bandgap. Under 1 sun illumination, WF3:PC 71 BM, WF3S: PC 71 BM, and WF3F:PC 71 BM OSCs with diphenyl ether (DPE) additive exhibited PCEs of 7.71, 7.91, and 9.11 %, respectively.…”
Section: Binary Fullerene-based Devicesmentioning
confidence: 99%
“…Under LED illumination of 500 lx, the devices showed PCEs of 12.83, 14.32, and 17.34 %, respectively. [30] Fullerene-based IOPVs have made great progress in recent years mainly ascribed to the development of large-bandgap donors. Generally, synthesizing wide-bandgap organic semiconductors with high absorption coefficients for further improving the performance of IOPVs is required.…”
Section: Binary Fullerene-based Devicesmentioning
confidence: 99%
“…In last few years, medium bandgap polymer/small molecule donors with fullerene-based acceptors reported IOPVs having PCEs of 8-28 % under indoor light illumination conditions. [14,17,19,[60][61][62] Yang et al investigated the P3HT polymer with different fullerene derivatives (PC 60 BM and ICBA) and obtained PCEs of 8.90 and 13.05 % for P3HT:PC 60 PB and P3HT:ICBA photoactive layers respectively, under 500 lux LED lamp. [60] The high performance of P3HT with ICBA compared to PC 60 BM acceptor material is due to better energy alignment.…”
Section: Indoor Organic Photovoltaic Materialsmentioning
confidence: 99%
“…As a result, WF3F:PC 71 BM BHJ can exhibit a PCE of 17.34 % with V OC : 0.69 V under 500 lux LED source. [62] Moreover, Shim et al demonstrated PDTBTBz-2F anti : PC 71 BM OPVs which exhibits an excellent spectrum matching with indoor lighting environment, resulting in an excellent power absorption ratio. [63] These optical properties contribute to performance of the PDTBTBz-2F anti :PC 71 BM based IOPVs with a high PCE of 23.1 % having V OC : 0.81 V under 1000 lux LED illuminations.…”
Section: Indoor Organic Photovoltaic Materialsmentioning
confidence: 99%
“…[ 1–6 ] An ideal bulk heterojunction (BHJ) adopted for indoor light harvesters should satisfy both the requirements of device performance and fabrication feasibility. [ 7–12 ] The power conversion efficiency (PCE) of IPV cells can be optimized by adjusting donor:acceptor (D:A) materials and weight fractions for the spectral matching with the indoor light sources (e.g., fluorescence, light‐emitting diode [LED], incandescent, and halogen lamps) and suitable energy levels. Together with appropriate solar cell fabrication methods, the open‐circuit voltage ( V oc ), short‐circuit current density ( J sc ), and fill factor (FF) values can be maximized under indoor light emissions.…”
Section: Introductionmentioning
confidence: 99%